Energy and Exergy Analysis of an Absorber Plate With Stainless Steel Scourers - Özgen, Filiz; Dayan, Ayşe; Yardımcı, Uğurcan; Kıstak, Celal; Celik, Nevin (My University, 2025)
In this study, energy and exergy efficiencies of collectors with stainless steel scourers as the surface enhancing elements were evaluated. Three surface types were tested according to the scourers' arrangement. T1 has the highest number of scourers in irregular arrangement. T2 has less scourers in regular row. T3 is the surface without scourers. Experiments were carried out at air flow rates of ?????=0,025 kg/s and ?????=0,05 kg/s. Ambient temperature, surface temperature, solar radiation, inlet-outlet temperatures of air were measured. The exergy efficiencies at ?????=0,025 kg/s kg/s are 50%, 48% and 40%, for T1, T2 and T3, respectively. These values reach up 66%, 55% and 52% at ?????=0,05 kg/s, for T1, T2 and T3 respectively. The results show that the flat plate collector (T3) has the lowest efficiency and highest irreversibility. It is also found that the increase in air flowrate improves the collector performance in general.
Keywords: Exergy; : Energy; Thermal Performance; Solar Energy Systems; Surface-enhancing elements